External and Internal Customer Perceptions on Quality of Health Services at the Dental and Oral Hospital of Mahasaraswati University Denpasar - Made Leonita Purnama Dewi; Rina Listyowati; Nyoman Mangku Karmaya (WMJ (Warmadewa Medical Journal), 2020)
Oral and dental health problems in Bali are still relatively high at 57.6%. As the only specialized dental hospital in Bali, RSGM needs to always maintain and improve the quality of health services, so as to increase people's desire for dental and oral care. This research was conducted to determine the quality of health services at the RSGM Mahasaraswati University Denpasar from the perspective of external and internal customers based on the five dimensions of Dabholkar, to find out the differences perceptions of external and internal customers based on the five dimensins of Dabholkar and their individual characteristics. This research is a cross sectional analytic. The sample was measured using a questionnaire with sample size of 112 external customers and 129 internal customers. The perception of external and internal customers on the quality of health services at the RSGM Mahasaraswati University Denpasar was mostly good: external customers (50.9%) and internal customers (52.0%). The results of statistical test analysis using chi-square (Î±=5%; p-value â‰¤0.05) found that there were differences in perception between external and internal customers in physical aspects (0.04) and policy (0.00); there were differences in perception of the age characteristics (0,00) and the level of education (0,03). External customer perceptions on the physical aspects, reliability, personal interaction, and problem solving were good, but in the policy dimension they had poor perceptions. Internal customers had good perceptions on the aspects of reliability, personal interaction, problem solving and policies, but on the physical aspects they had poor perceptions. Based on the age characteristics, there was a difference in perception; aged <28 years had a good perception, while those aged â‰¥28 years had less perception. RSGM Mahasaraswati Denpasar University needs to improve the quality of health services, especially in the physical and policy aspects so that can meet customer expectations. Key words: External and internal customer perception, quality of health services